Building Web apps with Ember.js write ambitious Javascript - Cravens, Jesse; Brady, Thomas (O'Reilly Media, 2014)
If you're a web developer interested in building scalable single-page applications - full-stack, browser-based apps that connect to a backend - this practical guide shows you how to use Ember.js, the popular JavaScript framework based on the model-view-controller (MVC) architectural pattern.